2022
DOI: 10.3390/ijerph19116537
|View full text |Cite
|
Sign up to set email alerts
|

The Comparative Effect of Reduced Mindfulness-Based Stress on Heart Rate Variability among Patients with Breast Cancer

Abstract: Heart rate variability (HRV) is a powerful tool for observing interactions between the sympathetic and parasympathetic nervous systems. This study evaluated HRV during a mindfulness-based stress reduction (MBSR) program among women with breast cancer after receiving treatment. A quasi-experimental, nonrandomized design was used. Patients were allocated to usual care (n = 25) and MBSR (n = 25) groups. HRV was measured using recognized methods to assess the autonomic nervous system. Two-way ANOVA and t-tests wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 57 publications
(67 reference statements)
0
4
0
Order By: Relevance
“…A lower HRV is often prevalent in cancer patients. Patients with higher HRV and coping mechanisms for stress have shown better adaptability [48,49] and more favorable prognosis, which has also been demonstrated in PDAC patients [50].…”
Section: Nutraceuticals-based Treatment Strategiesmentioning
confidence: 77%
“…A lower HRV is often prevalent in cancer patients. Patients with higher HRV and coping mechanisms for stress have shown better adaptability [48,49] and more favorable prognosis, which has also been demonstrated in PDAC patients [50].…”
Section: Nutraceuticals-based Treatment Strategiesmentioning
confidence: 77%
“…These improvements in coping skills and psychological functioning may be coupled with the normalization of physiological functioning, such as the autonomic nervous system, potentially leading to improved CV outcomes 29 . Despite this concept that autonomic regulation during stress may underlie the CV health benefits of MBSR, limited research has investigated this area, with existing data primarily relying on indirect markers of autonomic function [30][31][32] such as heart rate variability and plasma norepinephrine 33 , and largely focusing on resting-state activity. We now provide the first evidence that MBSR may modulate SNS response to acute mental stress in CKD, a patient population at increased CV risk by virtue of chronic SNS overactivation.…”
Section: Discussionmentioning
confidence: 99%
“…Although the mechanisms underlying the cardioprotective mechanisms of MBSR remain unknown, indirect evidence suggests that MBSR may lower BP by modulating autonomic nervous system activity, particularly by lowering SNS activity [27][28][29] . Earlier investigations using indirect measures of SNS activity have shown that meditation increases low frequency and high frequency heart rate variability [30][31][32] and lowers plasma norepinephrine levels 33 . In addition, our group previously measured direct, intraneural recordings of muscle sympathetic nerve activity (MSNA) via the gold-standard microneurographic technique to demonstrate the first direct evidence that a single session of mindfulness meditation acutely reduces BP and MSNA in patients with CKD 34 .…”
Section: Chronic Kidney Disease (Ckd) Afflicts More Than 35 Million I...mentioning
confidence: 99%
“…Patients' SDNN increased significantly after treatment, while patients demonstrated significant reductions in pain, perceived stress, anger and sleep disturbances. Wang, et al, [109] found significant differences in patients' SDNN, RMSSD and HF before and after the Mindfulness-Based Stress Reduction (MBSR) intervention. Consistent with the results of a review investigating the association between MBSR and HRV [110], i.e., a significant increase in time-domain-based SDNN and RMSDD and frequency-domain-based HF after 8 weeks of positive thinking training.…”
Section: Physical Behavior Interventionsmentioning
confidence: 99%